Minorities’ Rights and Laws in Pakistan: A Critical Analysis (Journal of Asian Development Studies, 2023)
Overall, the research's centre of attention is on the rights of minorities in Pakistan. Its chiefly briefs about the issues that minorities face in the country. This research aims to highlight the main problems that people other than the Muslim majority in Pakistan face in their daily lives. Observing the experiences of minorities in the country, the research is prepared. The more significant part of the research gives prominence to the major incidents practiced in the country. Moreover, the recent cases are deeply discussed in it. However, the government's positive concerns and practical actions on issues of minorities in the country are described. The legislation made by the legislators for the protection of the rights of minorities is considered. Furthermore, the research results will undoubtedly be the absolute source for learners. Over and above that, the people who are unaware of the situations regarding minorities in the country will get to know the facts and challenges that minorities have faced in the past and the improvements for them in the present. The research document analyses minority rights and the state's and politicians' behaviour towards them. It encompasses the laws and provisions of the constitution regarding the minorities' rights and their implementation on the ground level throughout the country.